Imagining Jewish authenticity : vision and text in American Jewish thought - Koltun-Fromm, Ken (Indiana University Press, 2015)
Exploring how visual media presents claims to Jewish authenticity, Imagining Jewish Authenticity argues that Jews imagine themselves and their place within America by appealing to a graphic sensibility. Ken Koltun-Fromm traces how American Jewish thinkers capture Jewish authenticity, and lingering fears of inauthenticity, in and through visual discourse and opens up the subtle connections between visual expectations, cultural knowledge, racial belonging, embodied identity, and the ways images and texts work together.